2014
DOI: 10.5152/dir.2013.13174
|View full text |Cite
|
Sign up to set email alerts
|

Fluorine-18 fluorodeoxyglucose PET-CT for extranodal staging of non-Hodgkin and Hodgkin lymphoma

Abstract: NUCLEAR MEDICINE AND MOLECULAR IMAGINGF-FDG PET-CT imaging, following a diagnostic contrast-enhanced CT (CE-CT) performed within the last month, were included in our study. A total of 129 PET-CT images, and all radiologic, clinical, and pathological records of these patients were retrospectively reviewed. RESULTSIn total, 137 hypermetabolic extranodal infiltration sites were detected by 18 F-FDG PET-CT in 62 of 110 patients. There were no positive findings by CE-CT that reflected organ involvement in 40 of 137… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 23 publications
(99 reference statements)
0
23
0
4
Order By: Relevance
“…The use of FDG‐PET has been well established as a modality in the staging and response assessment of HL in general 50‐52 . While only five cases were identified that specifically utilized FDG‐PET with CT or MRI for WR characterization in HL, the use of FDG‐PET imaging for the evaluation of WR in NHL has been well established 13,14 .…”
Section: Resultsmentioning
confidence: 99%
“…The use of FDG‐PET has been well established as a modality in the staging and response assessment of HL in general 50‐52 . While only five cases were identified that specifically utilized FDG‐PET with CT or MRI for WR characterization in HL, the use of FDG‐PET imaging for the evaluation of WR in NHL has been well established 13,14 .…”
Section: Resultsmentioning
confidence: 99%
“…In the present case, hysterectomy was performed because of the rapid worsening of the patient's neurological symptoms and the findings of the pelvic radiological examinations (PET/CT and MRI). PET/CT with Fluorine-18 fluorodeoxyglucose is now used in the diagnosis and staging of lymphoma [4] . It provides informations about lymphomatous extranodal involvement [4] .…”
Section: Discussionmentioning
confidence: 99%
“…PET/CT with Fluorine-18 fluorodeoxyglucose is now used in the diagnosis and staging of lymphoma [4] . It provides informations about lymphomatous extranodal involvement [4] . Maximum standard uptake value (SUVmax) increases with aggressiveness of the lymphoma [5] ; for high-grade Non Hodgkin Lymphoma (NHL), median SUVmax is about 20.6+/-14.2 [4] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Performance of FDG PET/CT in detecting bone marrow involvement was compared to contrast enhanced CT scan (CE-CT) in a prospective study by Omür et al [13], on a cohort of 110 patients with lymphoma (35 Hodgkin; 75 non-Hodgkin): they showed that CE-CT was falsely negative in 6 Hodgkin and 11 non-Hodgkin patients with bone marrow involvement on FDG PET/CT. All 17 cases were confirmed on BMB and successfully treated, with evidence of complete metabolic response on post-treatment PET/CT scans.…”
mentioning
confidence: 99%